A mathematical model to quantify the effect of water availability on soybean - Queiroz, Emilson França de; Milion, Luiz Carlos Baldicero; Minor, Harry Cameron; Neumaier, Norman (Pesquisa Agropecuaria Brasileira, 1996)
Utilizing results; of an experiment carried out with the soybean cultivars Paraná, Bossier and Santa Rosa, planted on four planting times (10/10; 11110; 12/10 and 0 1/10) through the agricultural years 1976177 to 1983/84, a mathematical model which quantifies the effect of water availability on soybean response to planting time was developed. The model indicated the critical periods for water deficiency and explained 52. 1%, 57.9% and 58.0% of the total variation observed in cultivars Paraná, Bossier and Santa Rosa, respectively. For the cultivar "Paraná", the subperiod R 1 - R4 was selected by the model as the most critical one for water deficiency. For "Bossier" and "Santa Rosa" cultivars, the model selected the periods RI - R4 and R4 - R6 as the most critical for water deficiency.